A CONSTRUÇÃO DA HISTÓRIA DEMOGRÁFICA NA HISTORIOGRAFIA PARANAENSE: A HISTORIADORA ALTIVA PILATTI BALHANA - Almeida, Letícia Leal de (2017)
The present work analyzes the historiographical production of Altiva Pilatti Balhana (1929-2009) understood from 1950, when the first interests of research arise, influenced by Geography and Anthropology, in the Faculty of Philosophy, Sciences and Letters and how Balhana delimited his interests in the history of immigration, integrating the faculty of the said Faculty in 1958, defending in 1959 his thesis of Free Teaching: Santa Felicidade: a process of assimilation. Balhana, together with Cecília Maria Westphalen (1927-2004), participated in the institutionalization of the Department of History of the University of Paraná in 1959, defined the bases and guidelines of the newly separated History of Geography and established an academic historiography at the University of Paraná. In the Department of History, Balhana and the other teachers organize a conception of History and the office of the historian who guided research projects, organization of sources and archives, especially from the reference of the Annales problem history. Balhana appropriated concepts and categories to apprehend the past, stemming from his interests in Immigration History, appropriated also the French Demographic History, developed by Louis Henry and Michel Fleury. Of the developments in the organization of historiography at the University of Paraná, a Postgraduate Program was created at Masters level in 1972, with a research line in Economic and Demographic History. Balhana and the other professors contributed to the consolidation and recognition of the historiography of the History Department of the University of Paraná, together with the Brazilian historiography.